Performance of Kampung Super chicken and Bangkok chicken first generation (G1) until the age of 12 weeks - Fetty Febriana Rahayu; Depison Depison; Gushairiyanto Gushairiyanto (Livestock and Animal Research, 2021)
Objective: The purpose of this research was to determine the performance of the first generation (G1) Kampung Super and Bangkok chicken aged 12 weeks.Methods: The research material were G1 Kampung Super and Bangkok chicken with 174 samples for each strain. This research was using the experimental method. The data collected included body weight, body weight gain, body measurements, and selected responses. The body weight, body weight gain, and body measurements data were analyzed using t-test independent, while the average value vector of body measured using T2-Hotelling test. Principal Component Analysis ware used to identify the characteristics of body shape and size.Results: The results of this study showed that body weight, body weight gain of DOC-4 weeks, 4-8 weeks, 8-12 weeks, and body measurements of G1 Kampung Super chickens were real different higher (P<0.05) than G1 Bangkok. The identifier of the size of the G1 Kampung Super and Bangkok chicken is the chest circumference. The characteristics of the shape G1 Kampung Super chicken is the length of the wings and the G1 Bangkok chicken is the lower body lenght. The selection response of G1 Kampung Super is higher than G1 Bangkok.Conclusions: The performance of G1 Kampung Super chicken was higher than G1 Bangkok chicken but the selection response value of G1 Bangkok chicken was higher than G1 Kampung Super chicken. The highest body weight gain of G1 Kampung Super and Bangkok chickens was achieved at the age of 8-12 weks.